Can local administration of humic acid shorten recovery time of mandibular fractures? Experimental study - Durmuş, Kasım; Bora, Adem; Doğan, Mehtap; Özer, Hatice; Tuncer, Ersin; Elif Altuntaş, Emine (ENT Updates, 2017)
Objective: The aim of the present pilot study was to evaluate the effects of a single local dose administration of humic acid on healing of subcondylar mandibular fractures in rats. Methods: In this study, a randomized experimental protocol was used. The study was conducted with 16 male Wistar-albino rats that were 16–18 weeks old. The rats (n=16) were randomly divided into two groups: Group HA received humic acid (0.3 cc/site, n=8) and Group C received no additional medical administration (control group, n=8). A full-thickness surgical osteotomy was performed in the subcondylar area. A single dose of humic acid (0.3 cc/site) was administered locally by spraying on the bone surfaces of the fracture line. Mandible was dissected on postoperative day 21. Then, fractured hemimandibles were obtained for histopathological examination. Results: The median score of bone fracture healing was 7.16 (range: 7 to 8) in the Group HA and 7.50 (range: 7 to 8) in the Group C. When the groups were compared in terms of bone healing scores, there was no statistical difference between the Group HA and the Group C (p>0.05). Conclusion: Results of this study showed that local administration of humic acid was not efficient for healing of bone fractures. However, we are of the opinion that it is required to conduct more comprehensive studies, including humic acid’s different concentrations and administration manners, evaluating the effects of humic acid on tissue both histopathologically and in terms of inflammatory and proinflammatory cytokine levels.